An annotated bibliography of 1 and 2 Thessalonians - Weima, Jeffrey A. D. (New Testament tools and studies, 1998)
This bibliography lists some 1300 works germane for the interpretation of 1 and 2 Thessalonians. It includes all relevant works written in the 20th century as well as a sizeable number of important sources from the 19th century. Virtually all the works listed are annotated, except for commentaries and dictionary articles. These annotations do not merely describe the content of each source but attempt to summarize its central thesis or argument. The works listed are classified and cross-indexed in such a way that the user is able to track down easily the relevant sources on any given topic or passage in the Thessalonian letters.